Quadcopter for Agricultural Use - Balakrishnan, N.; Kumar, R. Aravind; Narayanan, K. Sakthiya; Shanmugasudarm, R.; Sureshbabu, M.; Jeersath, H. Syeed (International Journal For Research In Mechanical & Civil Engineering, 2017)
The project goal was to design a semiautonomous Quad copter for the purpose of agricultural use. The Quad copter was designed to be small enough so that costs would be minimized. It is used for agricultural spraying, viewing and surveillance .The aerial Quad copter used for agricultural surveillance is an unmanned vehicle used for proper and accurate surveying of the crops and leaves reducing the human effort. The agricultural farm is surveyed by an infrared camera which will show the color image displaying the difference between infected or diseased crop and matured crop. The innovative foldable frame design developed will allow the Quad copter to be transported safely and with ease in a cylindrical shaped cushioned box packing. A tank is placed above the quad copter. By the use of tube the solution is supplied to sprayer. This paper introduce a quad copter which is used for pesticide spraying in agriculture field is handle by android application. Here the quad copter can be control through android phone for fertilizer spraying. This system reduces the problem related to the agricultural field and also improve the agricultural productivity.